PEMBERDAYAAN PETANI AGAR MAMPU MENGEMBANGKAN AGRIBISNIS (THE ENABLENSES OF FARMER TO BE ABLE TO DEVELOP AGRIBISNIS) - Widiputranti, Christine Sri (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2007)
Usually peasants have ability to increase agricultural productivity, but weakness in marketing, so they do not increase their income. More over, there are many peasants that always think risk minimization and not profit maximization. In order to become farmer that have ability to develop agribusiness, peasants empowering can be carried out by farmer gives agricultural extension to peasants.